Environment Detection and Path Planning Using the E-puck Robot - Muhammad Saleem Sumbal (Institute of Advanced Engineering and Science, 2016)
Automatic path planning is one of the most challenging problems confronted by autonomous robots. Generating optimal paths for autonomous robots are some of the heavily studied subjects in mobile robotics applications. This paper documents the implementation of a path planning project using a mobile robot in a structured environment. The environment is detected through a camera and then a roadmap of the environment is built using some algorithms. Finally a graph search algorithm called A* is implemented that searches through the roadmap and ﬁnds an optimal path for robot to move from start position to goal position avoiding obstacles